Miss Nelson is missing! - Allard, Harry; Marshall, James, 1942- (Boston : Houghton Mifflin, 1977)
The kids in Room 207 take advantage of their teacher$1 (Bs good nature until she disappears and they are faced with a vile substitute.s
Keywords: Schools -- Fiction; Behavior -- Fiction